2015
DOI: 10.1152/physrev.00030.2014
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Diabetes: The Increased Risk of Cancer and Cancer-Related Mortality

Abstract: Obesity and type 2 diabetes are becoming increasingly prevalent worldwide, and both are associated with an increased incidence and mortality from many cancers. The metabolic abnormalities associated with type 2 diabetes develop many years before the onset of diabetes and, therefore, may be contributing to cancer risk before individuals are aware that they are at risk. Multiple factors potentially contribute to the progression of cancer in obesity and type 2 diabetes, including hyperinsulinemia and insulin-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
434
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(501 citation statements)
references
References 216 publications
7
434
2
12
Order By: Relevance
“…Inflammation Interleukin-6 (IL-6) [1], [8] Many cell types such as immune cells, fibroblasts, and endothelial cells There is a complex relationship between IGF-1 and obesity or obesity-related diseases [16], [17], [18]. However, regarding the pathogenesis of obesity-related cancers, a plausible explanation has been proposed [18], [19], [20].…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation Interleukin-6 (IL-6) [1], [8] Many cell types such as immune cells, fibroblasts, and endothelial cells There is a complex relationship between IGF-1 and obesity or obesity-related diseases [16], [17], [18]. However, regarding the pathogenesis of obesity-related cancers, a plausible explanation has been proposed [18], [19], [20].…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%
“…However, regarding the pathogenesis of obesity-related cancers, a plausible explanation has been proposed [18], [19], [20]. The inflammatory situation in obesity perhaps creates a state of insulin resistance where cells cannot utilize glucose appropriately due to the defective response to insulin.…”
Section: Chiefly Produced By Receptor Functionmentioning
confidence: 99%
“…Insulin resistance appears to play a central role in endometrial carcinogenesis. Therefore, treatment with insulin-sensitizing agents that act through reducing insulin levels could offer a general approach to prevent the development of cancer and reduce metastasis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Although hyperinsulinemia, hyperglycemia and chronic inflammation may be significant mechanisms in the neoplastic process of a number of types of cancer, the carcinogenic mechanisms induced by DM in NETs remain to be elucidated (23). A Taiwanese population-based study revealed that diabetes was associated with a significantly higher risk of lung cancer (24).…”
Section: Discussionmentioning
confidence: 99%